Involvement of Peripheral Beta-Endorphin and MU, Delta, Kappa Opioid Receptors in Electro Acupuncture Analgesia for Prolonged Inflammatory Pain of Rats. (May 2013) - Fang, J.Q.; Jiang, Y.L.; Qiu, S.C.; He, X.F.; Huang, L.; Shen, Y.F.; Yin, X.H.
Acupuncture is commonly used to relieve chronic pain worldwide. Accumulating evidence shows that peripheral opioid system plays an important role in inhibiting inflammatory pain. This study aimed to investigate the involvement of peripheral opioid system in electroacupuncture (EA) analgesia for prolonged inflammatory pain. Inflammatory pain was induced by an intraplantar injection of complete Freund's adjuvant (CFA) into the right hind paw. EA (2/100 Hz, 2 mA) was applied to the ipsilateral Zusanli (ST36) and Kunlun (BL 60) acupoints for 30 min once everyday. Block studies on EA analgesia were performed on day 18 after CFA injection by using α-helical corticotrophin-releasing factor (CRF), a CRF antagonist, and naloxone methiodide, a peripherally restricted opioid receptor antagonist. Paw withdrawal latency (PWL) to a noxious thermal stimulus was measured as the pain behavioral change. Radioimmunoassay for beta-endorphin (beta-END), Met-enkephalin (Met-ENK), and dynorphin A (DYN A) in paw inflammatory tissue and immunohistochemistry study for mu, delta, kappa opioid receptors in dorsal root ganglion (DRG) were carried out. A subsequent validation experiment by locally delivered exogenous beta-END was also performed. We found that EA significantly increased the PWL of rats injected with CFA from day 4 to day 18. Locally administered α-helical CRF or naloxone blocked EA-produced analgesia. EA increased beta-END level in the paw inflammatory tissues, while CFA raised the local levels of Met-ENK and DYN A. The increased beta-END level by EA was fully reversed by α-helical CRF. Intraplantar injection of exogenous beta-END alleviated prolonged inflammatory pain. EA also up-regulated the expressions of mu, delta, kappa opioid receptors in rat L5 DRG. In conclusion, peripheral local beta-END and three subtypes of opioid receptors may be involved in EA analgesia for prolonged inflammatory pain.